Reference for the Remote User Through Embedded Librarianship. Issue 3 (2nd July 2016) - Connolly-Brown, Maryska; Mears, Kim; Johnson, Melissa E.
ABSTRACT: Embedded librarians serve an important role in assisting remote users. Despite the varying degrees of embeddedness, all maintain the goal of ensuring the same high-quality reference and instruction services that users have come to expect from the traditional library setting. Embedded librarians select and use technology that most effectively meets the needs of this unique user group. This technology can include the library Web site, course management systems, research guides, lecture and screen capture software, remote reference (including telephone, chat, and email), web conferencing, online survey tools, citation management, and social media.